Pulmonary arterial hypertension associated with rare cause of ANCA-associated vasculitis misdiagnosed as idiopathic one - Li, Yi (Int J Clin Exp Med, 2015)
Pulmonary arterial hypertension (PAH) and ANCA-associated vasculitis (AAV) are both rare and complex diseases with poor prognosis especially when misdiagnosis. We report a rare case of a young woman presented with idiopathic pulmonary arterial hypertension (IPAH), but who was later found to have PAH associated with AAV. This case reminds us the very importance of differential diagnosis to PAH patients and the identification of rare cause likes ANCA-associated vasculitis. To our knowledge, this patient represents the first published case of misdiagnosis of PAH secondary to ANCA-associated vasculitis.